If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying logx + 3 = 1 + -1logx Reorder the terms: 3 + glox = 1 + -1logx Solving 3 + glox = 1 + -1glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glox' to each side of the equation. 3 + glox + glox = 1 + -1glox + glox Combine like terms: glox + glox = 2glox 3 + 2glox = 1 + -1glox + glox Combine like terms: -1glox + glox = 0 3 + 2glox = 1 + 0 3 + 2glox = 1 Add '-3' to each side of the equation. 3 + -3 + 2glox = 1 + -3 Combine like terms: 3 + -3 = 0 0 + 2glox = 1 + -3 2glox = 1 + -3 Combine like terms: 1 + -3 = -2 2glox = -2 Divide each side by '2lox'. g = -1l-1o-1x-1 Simplifying g = -1l-1o-1x-1
| Y=log1/5(x-6) | | 3y-3*8=24 | | 2(-1.4-1.8y)-4y=20 | | 4r-2s+2r-6s= | | Y(4)=7 | | 0.666(6x+30)=x+5(x+4)-2x | | 9r-3=69 | | RSZ=5n+6 | | 4-rad(31-3x)=rad(-6-2x) | | X^2=8x+105 | | 8s-2r+5s-8r= | | 4-2(x+5)+7=-11 | | .3x+5x+4-x+7=88 | | 6n^2-105=9n | | 200m-125m+42750=45675-150m | | 7y-8=3y+2 | | 6r-22=18+r | | N(2)=19 | | 7n^2-8=-12n | | 5(1-2w)=-25 | | 2(x+3)+x=5x | | 5m-10=3m-12 | | 5=x+(-2) | | 2.7y+y= | | 6x+1=16+3x | | 4=n-4 | | (a-9)(a-19)=a | | 7n^2-8=-12 | | 12=10+r | | 10x-8=6x-20 | | 4=a-6 | | 4=a+6 |